Qualitative lysine crotonylation and 2-hydroxyisobutyrylation analysis in the ovarian tissue proteome of piglets - Yang, Diqi; Li, Xiaoping; Yu, Beibei; Peng, Hui (Frontiers in Cell and Developmental Biology, 2023)
Ovarian function influences diverse aspects of fertility and reproductive lifespan by regulating oocyte supply and hormone secretion. Lysine crotonylation (Kcr) and lysine 2-hydroxyisobutyryllysine (Khib) are newly identified post-translational modifications and function as regulators of transactivation in mammals. In this study, we investigated protein post-translational Kcr and 2-hydroxyisobutyrylation in the ovarian tissues of piglets. A total of 653 overlapping proteins among differentially modified proteins were identified for both crotonylation and 2-hydroxyisobutyrylation. Gene Ontology enrichment analysis indicated that 653 DMPs were significantly enriched in nucleosome organization, chromatin assembly, DNA packaging, peptide biosynthetic process and peptide metabolic process. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis showed enrichment in proteasome, ribosome, fatty acid elongation, pyruvate metabolism and pentose phosphate pathway. Fifteen DMPs were identified in the proteasome pathway, of which PSMC6 and PSMB7 were the core proteins. In addition, the significant changes in Kcr and Khib in the complex subunits of the proteasome may be involved in cell cycle processes during oocyte development. Forty-four DMPs with both Kcr and Khib modifications were related to the ribosome pathway. The regulated ribosome pathway may indicate that Kcr and Khib comodified proteins participate in protein synthesis during oocyte development. Western blot and immunofluorescence staining results supported the reliability of the sequencing results. Our results may provide a valuable resource to help illuminate the roles of Kcr and Khib in ovarian development and may serve as new tools to better control diseases.